TINJAUAN SOSIOLOGIS: FUNGSI SOSIAL GURU PENDIDIKAN AGAMA ISLAM DI TENGAH MASYARAKAT - Ghofur, Abdul; Firliatul Ilahi, Rani; Rudianto; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2025)
This study aims to explore the social role of Islamic Religious Education (PAI) educators using a field-based case study approach, supplemented with data from Probolinggo City, an urban area characterized by strong religiosity and rapid social, cultural, and technological development. PAI educators in this region are not merely instructors of religious teachings within educational settings but also social actors who make crucial contributions to shaping students’ personalities, fostering religious tolerance, and maintaining social harmony in a diverse community. By employing a field-based case study methodology, this research draws on official information from the Probolinggo City Ministry of Religious Affairs, the Education Office, the PAI Teachers’ Working Group (MGMP PAI), as well as relevant academic literature to provide a comprehensive portrayal of PAI educators’ responsibilities. The findings reveal that PAI educators perform extensive social roles, ranging from instilling educational ethics, addressing social failures, developing digital norms, to actively participating in community activities. Challenges such as the influence of technological information, declining moral values among youth, and social diversity hinder the effectiveness of PAI educators’ functions. Therefore, collaboration among educational institutions, households, and religious social organizations is a key element in enhancing the role of PAI educators in fostering a morally upright and balanced generation.